The triple impact of Enoxaparin: Moderating comorbidities, reducing hospitalization, and rationalizing medications - Ali, Y. J.; Mohammad, N. B. A.; Faisal, I. M.; Merkhan, M. M. (Regulatory Mechanisms in Biosystems, 2025)
Enoxaparin is a low molecular weight heparin which has revealed clinical efficacy through its anticoagulant properties. While it has been thoroughly investigated for coagulation prophylaxis and treatment, its therapeutic role in multiple domains of patient care remain s underexplored. This study sought to evaluate the integrated role of E noxaparin therapy on three healthcare domains: comorbidity management, hospitalization rates, and medication optimization in diverse patient popul a tions. In this prospective observational study, the data were collected directly from patients. A record w as placed for each patient to collect their demographic parameters, Enoxaparin dose, admission date, hospitalization stays and compelling diseases. A total of 125 subjects enrolled in the present study (age 58.2 ± 15.4 years, male 54.4% and females 45.6%). Enoxaparin was used at a daily dose 5280 ± 1147 IU (range 4000 – 8000 IU) with most patients receiving their dose once or twice daily . The m ajority of patients (71.2%) were administered E noxaparin for therapeutic purposes and 28.8% receiv ed prophylactic doses. Gender differences showed non-significant age-related effects ( P = 0.320), with 20 male (16 .0 %) p a tients in the younger group and 29 (23.2%) patients in the older group (>60) , while females were equally matched in each age category. The duration of therapy with E noxaparin demonstrated a non-significant ( P = 0.675) difference between prophylaxis (3.2 ± 2.6 days) and treatment groups (3.4 ± 2.6 days). E noxaparin was mainly indicated for treatment rather than prophylaxis, with the polypharmacy group showing the highest utilization (60.8% for treatment compared to 23.2% for prophylaxis). The d uration of E noxaparin therapy increased non-significantly with polypharmacy severity (2.4 ± 1.5 days in the non-polypharmacy group to 6.3 ± 3.6 days in the hyperpolypharmacy group). The number of medications increased across groups: 3.7 ± 0.5 in non-polypharmacy, 7.6 ± 1.6 in polypharmacy, and 12.2 ± 1.4 in hyperpolypharmacy patients. The hospitalization duration followed similar trends, 2.4 ± 1.5 days in non-polypharmacy patients to 5.8 ± 3.5 days in hyperpolypharmacy patients. The m ajority of patients ha d good outcomes, with the polypharmacy group (99 patients, 79.2%) having the most favourable outcomes . Enoxaparin revealed extensive properties outside its anticoagulant role, pr o viding clear benefits to patient s through comorbidity reduction, hospitalization moderation, and medication optimization. These findings suggest that strategic utilization of E noxaparin may enhance overall healthcare efficiency while improving patient outcomes across multiple therapeutic domains. The triple effects of E noxaparin make it worthy of consideration as a multifaceted therapeutic biomolecule in patient individualized complexity, potentially integrating the care of patients and proper utilization of healthcare resources.